Evaluation Of Antimicrobial and Cytotoxic Properties of Chondroitin Sulphate Based Hydrogel Incorporated with Dihydroxyacetone Phosphate, Copper Nanoparticles and Quercetin - Yuvaraj, Ashna; Ganesh S, Balaji (Journal of Neonatal Surgery, 2025)
Introduction: Chondroitin sulfate, a natural component found in connective tissues and cartilage, possesses intrinsic antioxidant capabilities. These properties stem from its capacity to counteract free radicals, inhibit the activities of reactive oxygen species (ROS), and reduce oxidative stress within the local environment. The aim of the study is to evaluate the antimicrobial and cytotoxic properties of chondroitin sulphate based hydrogel incorporated with dihydroxyacetone phosphate, copper nanoparticles and quercetin. Materials and methods: 10% chondroitin sulphate was methacrylated using methacrylic acid, and then supplemented with Cu nanoparticles and dihydroxyacetone phosphate/quercetin. The resulting solution was photocrosslinked using the photoinitiator I2959 to form a gel, which was subsequently freeze-dried. The lyophilized material was analyzed for swelling and degradation properties, tested for antimicrobial effects, and evaluated for cell compatibility using the MTT assay. RESULTS: The culture plates show clear zones of inhibition around the hydrogel sample, indicating moderate antibacterial activity. This suggests that the Cu nanoparticles and quercetin incorporated in the formulation may effectively reduce bacterial growth, which is beneficial for applications in wound healing and implantable biomaterials.The control sample showed a viability of 91.2%, while the test sample recorded a slightly higher value of 93.6%. These characteristics are desirable in injectable hydrogels, as they improve adaptability to tissue architecture and enable better control over the material’s resorption and drug release. CONCLUSION: In conclusion, the incorporation of Cu and DAP nanoparticles, along with quercetin, into CS- based injectable hydrogels holds great potential for the development of advanced biomaterials with enhanced antimicrobial and cytotoxic properties